Cyclization mechanism of phomopsene synthase: mass spectrometry based analysis of various site-specifically labeled terpenes - Shinde, Sandip S.; Minami, Atsushi; Chen, Zhi; Tokiwano, Tetsuo; Toyomasu, Tomonobu; Kato, Nobuo; Sassa, Takeshi; Oikawa, Hideaki (Journal of Antibiotics, 2017)
Elucidation of the cyclization mechanism catalyzed by terpene synthases is important for the rational engineering of terpene cyclases. We developed a chemoenzymatic method for the synthesis of systematically deuterium-labeled geranylgeranyl diphosphate ( GGPP), starting from site-specifically deuterium-labeled isopentenyl diphosphates (IPPs) using IPP isomerase and three prenyltransferases. We examined the cyclization mechanism of tetracyclic diterpene phomopsene with phomopsene synthase. A detailed EI-MS analysis of phomopsene labeled at various positions allowed us to propose the structures corresponding to the most intense peaks, and thus elucidate a cyclization mechanism involving double 1,2-alkyl shifts and a 1,2-hydride shift via a dolabelladien-15-yl cation. Our study demonstrated that this newly developed method is highly sensitive and provides sufficient information for a reliable assignment of the structures of fragmented ions.